1999
DOI: 10.1210/en.140.11.5195
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Estrogen Receptor   and   Messenger Ribonucleic Acids in Adult Gonadotropin-Releasing Hormone Neurons

Abstract: The behavior of the gonadotropin-releasing hormones (GnRH) neurons controlling fertility is dependent upon cyclic fluctuations in circulating concentrations of estrogen. However, the nature of estrogen action upon these cells has remained controversial due to their dispersed distribution within the brain, and evidence indicating that they do not express nuclear estrogen receptors (ERs) in vivo. We report here an acute brain slice preparation that enables individual living GnRH neurons to be identified within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
1
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 0 publications
9
111
1
4
Order By: Relevance
“…Examination of the GnRH-1 neuronal population in vitro revealed increases in intracellular calcium, observed with calcium imaging, that correlate with GnRH-1 release (Terasawa et al, 1999a;Moore and Wray, 2000), that display species-specific synchronized calcium oscillations with periodicities similar to GnRH-1 release in vivo (Terasawa et al, 1999b;Moore et al, 2002), and that are maintained in the absence of synaptic input (Moore et al, 2002). Recent studies indicate that a subpopulation of GnRH-1 neurons in vitro coexpresses ER␤ (Sharifi et al, 2002), with the percentage in vitro similar to that found in vivo (Skynner et al, 1999). Thus, GnRH-1 neurons in this in vitro system maintain many intrinsic characteristics of GnRH-1 neurons in vivo (Fueshko and Wray, 1994;Wray 2002).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Examination of the GnRH-1 neuronal population in vitro revealed increases in intracellular calcium, observed with calcium imaging, that correlate with GnRH-1 release (Terasawa et al, 1999a;Moore and Wray, 2000), that display species-specific synchronized calcium oscillations with periodicities similar to GnRH-1 release in vivo (Terasawa et al, 1999b;Moore et al, 2002), and that are maintained in the absence of synaptic input (Moore et al, 2002). Recent studies indicate that a subpopulation of GnRH-1 neurons in vitro coexpresses ER␤ (Sharifi et al, 2002), with the percentage in vitro similar to that found in vivo (Skynner et al, 1999). Thus, GnRH-1 neurons in this in vitro system maintain many intrinsic characteristics of GnRH-1 neurons in vivo (Fueshko and Wray, 1994;Wray 2002).…”
Section: Introductionsupporting
confidence: 57%
“…ER␤ plays a functional role in the neuroendocrine system of both peripubertal (Temple et al, 2003) and adult mice (Abraham et al, 2003). Recent reports indicate that a subpopulation of GnRH-1 neurons contains ER␤ transcript (Skynner et al, 1999;Sharifi et al, 2002) and protein (Hrabovsky et al, 2001), consistent with a possible direct action of E2, via ER␤, on GnRH-1 neurons.…”
Section: Introductionmentioning
confidence: 93%
“…Direct action of estradiol may be possible as GnRH neurons in rats and mice express mRNA of the estrogen receptor (ER) ␤-isoform (ER␤) (56,57), although nuclear ER␤ immunoreactivity has not been found in mouse GnRH neurons. § Although the role of ER␤ in LH surge regulation remains unclear, ER␤ knockout mice show normal LH levels (58), and disruptions to fertility in ER␤ knockouts, such as reduced litter size, appear to be due to effects on the ovary rather than at the level of the hypothalamus or pituitary (59).…”
Section: Discussionmentioning
confidence: 99%
“…However, since initial efforts aimed at detecting AR and ER in GnRH neurons failed (Huang andHarlan, 1993, Shivers et al, 1983),, many investigators concluded that the effects of steroid hormones on GnRH were mediated indirectly (Herbison et al, 1995;Herbison and Theodosis, 1992;Lehman and Karsch, 1993). However, the identification of ERbeta resurrected this longstanding hypothesis, as several laboratories subsequently showed the co-expression of GnRH and ERβ (Hrabovszky et al, 2000;Hrabovszky et al, 2001;Kallo et al, 2001;Skynner et al, 1999). Nonetheless, evidence for a functional role for ERbeta in regulating GnRH neuronal function in vivo is still forthcoming.…”
Section: Other Roles For 3beta -Diol In Brain Functionmentioning
confidence: 99%